Clinical Analysis of Discharge Patterns from HSC Hosptials in Northern Ireland during early 2020 and any Link with COVID-19 Outbreaks in Care Homes : A report to the Minister of Health.: A report to the Minister of Health. (2020) - Herity, Niall
No abstract available